RNF213 inhibits migration in lung adenocarcinoma cell: RNF213 hinders lung adenocarcinoma cell migration - Liu, Xiaoli; Zeng, Huanwen; Li, Zizi; Wei, Chunren; Zhang, Zhaoyuan; Liu, Xiaodong; Chen, Nan (Cellular and Molecular Biology, 2023)
Non-small cell lung cancer (NSCLC) is one of the most common malignant tumors, and lung adenocarcinoma (LUAD) accounts for up to 40% of NSCLC. Ring finger protein 213(RNF213) has been demonstrated to suppress several cancers, including glioblastoma and breast cancer. Nonetheless, the role of RNF213 in LUAD has not been investigated. The expression of RNF213 in LUAD tissues was analyzed by western blotting, The Cancer Genome Atlas, Genotype Tissue Expression Project, and Gene Expression Omnibus databases. Prognostic value analysis was performed through the Kaplan-Meier Plotter database. We determined the role of RNF213 in LUAD cells through cell counting kit‑8 assay, migration, and invasion assay. The clinical roles of RNF213 were evaluated by immunohistochemical staining assay (IHC) and Kaplan-Meier survival analysis. RNF213 expression was reduced in LUAD, thus affecting the prognosis of LUAD. And RNF213 could suppress the migration and invasion of LUAD cells to prevent tumor development. the expression of RNF213 is positively correlated with the overall survival, providing a novel marker in the prognosis of LUAD patients.